The Global Community yearbook of international law and jurisprudence 2021 - Ziccardi Capaldo, Giuliana (New York, NY : Oxford University Press, 2023)
The 2021 edition of 'The Global Community Yearbook of International Law and Jurisprudence' is a thorough annual survey of major developments in international courts. General Editor Giuliana Ziccardi Capaldo selects excerpts from important court opinions, supported by contributors who provide expert guidance on those cases. The topical organisation and subject index make the thorough, comprehensive content easy to navigate.
Also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on February 2, 2023).
Keywords: International law -- Periodicals; Jurisprudence -- Periodicals; Law; International law